2017
DOI: 10.1128/aac.00270-17
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Dispersion of Azole Resistance in Aspergillus fumigatus: Fatal Invasive Aspergillosis in a Patient with Acute Myeloid Leukemia Infected with an A. fumigatus Strain with a cyp51A TR 46 Y121F M172I T289A Allele

Abstract: This Journal section presents a real, challenging case involving a multidrugresistant organism. The case authors present the rationale for their therapeutic strategy and discuss the impact of mechanisms of resistance on clinical outcome. An expert clinician then provides a commentary on the case.ABSTRACT Patients with hematologic malignancies as well as allogeneic hematopoietic stem cell transplantation (HSCT) patients are at high risk for invasive aspergillosis. Here, we report a culture-and autopsy-proven fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
(29 reference statements)
0
10
0
Order By: Relevance
“…We report the presence of TR 46 /Y121F/T289A now also from Iran, where until now only TR 34 /L98H had been isolated . This mutation, conferring voriconazole resistance, has been reported from both environmental (China, Taiwan, United Kingdom, Colombia, France, Germany, India, the Netherlands and Tanzania) and clinical sources (Spain, United Kingdom, France, Portugal, Argentina, Taiwan, Germany, China, Japan, United States, Denmark, Belgium and the Netherlands) (Table 1). All previous studies conducted in Iran for monitoring the mechanism of resistance among azole‐resistant A fumigatus in both clinical and environmental samples showed that the TR 34 /L98H mutation was reported with increasing frequency from 3.3% in 2013 to 6.6% in 2016 .…”
Section: Discussionmentioning
confidence: 73%
“…We report the presence of TR 46 /Y121F/T289A now also from Iran, where until now only TR 34 /L98H had been isolated . This mutation, conferring voriconazole resistance, has been reported from both environmental (China, Taiwan, United Kingdom, Colombia, France, Germany, India, the Netherlands and Tanzania) and clinical sources (Spain, United Kingdom, France, Portugal, Argentina, Taiwan, Germany, China, Japan, United States, Denmark, Belgium and the Netherlands) (Table 1). All previous studies conducted in Iran for monitoring the mechanism of resistance among azole‐resistant A fumigatus in both clinical and environmental samples showed that the TR 34 /L98H mutation was reported with increasing frequency from 3.3% in 2013 to 6.6% in 2016 .…”
Section: Discussionmentioning
confidence: 73%
“…The difference in sensitivity from biopsies was also not significant ( p = 0.081). The TR46/Y121F/T289A mutation combination was found in a lung biopsy sample of a patient suffering from AML and described in Rössler et al ( 2017 ). Furthermore, we detected three L98H mutations and one TR34 alteration using our in-house ARAf PCRs with subsequent DNA sequencing.…”
Section: Resultsmentioning
confidence: 79%
“…The isolate showed the following MIC (minimum inhibitory concentration) values obtained by EUCAST reference microdilution method: voriconazole 2.0 mg/L, itraconazole >16.0 mg/L, posaconazole 0.5 mg/L (Hamprecht et al, 2012 ). The second triazole resistant TR46/Y121F/M172I/T289A positive A. fumigatus strain was from the Institute for Medical Microbiology, University Medical Center Göttingen, Göttingen, Germany (originated from the Institute of Medical Microbiology and Hygiene, Technische Universität Dresden, Dresden, Germany) and showed the following EUCAST MIC values: voriconazole >32 mg/L, itraconazole 1 mg/L, posaconazole 0.5 mg/L (Rössler et al, 2017 ). Characterization of the third multi-azole resistant TR46/Y121F/T289A positive clinical isolate (IMMi2107) from the Institute of Medical Microbiology, University Hospital Essen, Essen, Germany revealed the following EUCAST MIC values: itraconazole >16.0 mg/L, voriconazole 2 mg/L, posaconazole 0.5 mg/L (Steinmann et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 126 Rößler (2017) Aspergillus fumigatus Invasive pulmonary aspergillosis with multiple fungal abscesses A patient in his early 70s with progressive AML AMB and voriconazole No CT scan and BAL fluid culture Died Azole resistance in A. fumigatus is an increasingly important phenomenon, leading to breakthrough infections despite prophylaxis. 127 Antonogiannaki (2019) Aspergillus species Invasive Aspergillus tracheobronchitis A 50-year-old with hairy cell leukemia and previous Plasmodium falciparum infection AMB No High resolution CT, BAL examination and direct smear Died Previous P. falciparum infection was an additional predisposing factor for the manifestation of Aspergillus infection. 128 Turki (2017) Aspergillus spp.…”
Section: Aspergillosismentioning
confidence: 99%